Effect of glycemic index meals on recovery and subsequent endurance capacity - Wong, S. H.; Chen, Y. J.; Fung, W. M.; Morris, J. G. (International Journal of Sports Medicine, 2009)
This study examined the effect of ingesting a high or low glycemic index (GI) meal during a short-term recovery period on endurance running capacity. On two occasions, seven men (age 30.0±2.6 yr, body mass 60.7±1.4 kg, VO2max 62.1±2.2 ml·kg-1·min-1) ran at 70% VO2max on a level treadmill for 90 min (R1), followed by a 4 h recovery (REC) and a further exhaustive run at the same speed (R2). Twenty minutes after R1, each subject consumed an isoenergetic meal containing either high GI (HGI, GI=77) or low GI (LGI, GI=37) carbohydrate providing 1.5 g CHO·kg-1 BM. During REC, subjects also ingested a prescribed volume of water equal to 150% of their BM loss during R1. The duration of R2 in the HGI trial was 15% longer than in the LGI trial (HGI: 86.6±10.7 min vs. LGI: 75.2±8.1 min, p<0.05). The subjects also achieved complete rehydration after REC on both occasions. In conclusion, the consumption of a HGI meal during a 4 h recovery improved endurance capacity in a subsequent run; however, the precise mechanism(s) by which this takes place is yet to be clarified.